Cigarette tar yields in relation to mortality from lung cancer in the cancer prevention study II prospective cohort, 1982-8. Issue 7431 (8th January 2004) - Harris, Jeffrey E; Thun, Michael J; Mondul, Alison M; Calle, Eugenia E
Abstract: Objective To assess the risk of lung cancer in smokers of medium tar filter cigarettes compared with smokers of low tar and very low tar filter cigarettes. Design Analysis of the association between the tar rating of the brand of cigarette smoked in 1982 and mortality from lung cancer over the next six years. Multivariate proportional hazards analyses used to assess hazard ratios, with adjustment for age at enrolment, race, educational level, marital status, blue collar employment, occupational exposure to asbestos, intake of vegetables, citrus fruits, and vitamins, and, in analyses of current and former smokers, for age when they started to smoke and number of cigarettes smoked per day. Setting Cancer prevention study II (CPS-II). Participants 364 239 men and 576 535 women, aged 30 years, who had either never smoked, were former smokers, or were currently smoking a specific brand of cigarette when they were enrolled in the cancer prevention study. Main outcome measure Death from primary cancer of the lung among participants who had never smoked, former smokers, smokers of very low tar cigarette filter, low tar (8-14 mg) filter, high tar (22 mg) non-filter brands and medium tar conventional filter brands (15-21 mg). Results Irrespective of the tar level of their current brand, all current smokers had a far greater risk of lung cancer than people who had stopped smoking or had never smoked. Compared with smokers of medium tar (15-21 mg) filter cigarettes, risk was higher among men and women who smoked high tar (≥22 mg) non-filter brands (hazard ratio 1.44, 95% confidence interval 1.20 to 1.73, and 1.64, 1.26 to 2.15, respectively). There was no difference in risk among men who smoked brands rated as very low tar (1.17, 0.95 to 1.45) or low tar (1.02, 0.90 to 1.16) compared with those who smoked medium tar brands. The same was seen for women (0.98, 0.80 to 1.21, and 0.95, 0.82 to 1.11, respectively). Conclusion The increase in lung cancer risk is similar in people who smoke medium tar cigarettes (15-21 mg), low tar cigarettes (8-14 mg), or very low tar cigarettes (≤ 7 mg). Men and women who smoke non-filtered cigarettes with tar ratings 22 mg have an even higher risk of lung cancer.